The Transformation of Labour Law in Europe : A Comparative Study of 15 Countries, 1945-2004 - Verge, Pierre (Relations industrielles / Industrial Relations, 2010)
The article reviews the book, "The Transformation of Labour Law in Europe : A Comparative Study of 15 Countries, 1945-2004," edited by Bob Heppel and Bruno Veneziani.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z